Philosophical Aspects of Developing the Professional-Ethical Culture of Doctors in the Metamodern Era - Yevtushenko, Yuliia (Journal of Education Culture and Society, 2025)
Aim. The article aims to study the influence of metamodern philosophy on the development of doctors’ professional-ethical culture through innovative pedagogical strategies. Methods. Conceptual and comparative analysis of scholarship on medical ethics, philosophy of medicine and medical education; systematisation and modelling; axiological and competence-based approaches; hermeneutic interpretation of sources; and a narrative review of recent studies. Result. The study shows that metamodernism’s oscillation between idealism and pragmatism enables a pedagogical model for developing doctors’ professional-ethical culture. The model combines traditional ethics with adaptive strategies to modern challenges and proves effective through simulations, role-playing, and interdisciplinary approaches. Conclusion. Metamodernist philosophy plays a key role in shaping doctors’ professional-ethical culture by integrating oscillation, pragmatism, and multiple perspectives into pedagogy. Such approaches foster ethical competence through simulations, role-play, and interdisciplinary methods that develop critical thinking and flexibility. The model’s strengths (integrative, adaptable, reflective) outweigh the challenges of assessment and resistance to tradition, while future research will refine its use in medical education. Research restrictions. The study is theoretical; conclusions are derived from secondary sources and conceptual modelling without empirical testing. Applicability across institutions and cultural settings may vary; further validation via pilot implementations and statistical evaluation is required. Cognitive value. The synthesis of metamodernist philosophy with medical pedagogy opens new ways to develop doctors’ ethical consciousness amid contemporary challenges. It deepens understanding of how cultural change shapes professional competencies and offers guidance for adapting training to current realities.